Determinants and Complexities of Halal Logistics in Malaysia: A Systematic Literature Review - Husna, Anis; Yusof, Mohd Faiz Mohamed; Jafar, Ahmad; Qadri, Ahmed Qasim (Muslim Business and Economics Review, 2024)
This study employs a systematic literature review to examine the challenges of halal logistics in Malaysia, addressing a significant gap in the literature concerning the operational difficulties in maintaining halal integrity throughout supply chain processes. As the world’s Muslim population grows, understanding the complexities of halal logistics becomes crucial for industry stakeholders. Through Google Scholar and Scopus databases, this research identifies and analyzes 14 pertinent articles, focusing on the challenges within halal logistics. The thematic analysis reveals six primary challenges faced in Malaysia: high operational costs, lack of knowledge, limited demand for halal logistics services, operational complexities, inadequate management, and difficulties in the implementation of halal standards. These findings not only enhance the theoretical understanding of halal logistics but also offer practical insights for improving its implementation. By pinpointing these challenges, the study suggests a need for strategic efforts to foster market growth and service competitiveness in the halal logistics sector. Future research should broaden the review scope and explore solutions to these challenges, promoting best practices in halal logistics.